Ecological Interface Design for Anaesthesia Monitoring - Watson, Marcus; Russell, W. John; Sanderson, Penelope (Australasian Journal of Information Systems, 2000)
The operating theatre is a noisy place with many uninformative and redundant alarms. Using data from a recent observational study, we demonstrate that anaesthetists actively respond to only 3.4% of all audible alarms. We outline a range of possible solutions to the alarm problem. Ecological Interface Design (EID) helps to outline the requirements for an information environment for anaesthetists and to indicate the possible benefits of continuous auditory signals. Our observational data are then "reworked" to give an indication of possible benefits of a continuous auditory display. Finally we indicate steps we are taking to test these ideas empirically